The Status of Micronutrients and Sulphur in some Plantation Crops at Different Ages in an Alfisol of Southern Nigeria - Ogeh, Joseph Sunday; Ipinmoroti, Rotimi Rufus (UNIVERSITY OF LAMPUNG, 2014)
A study was conducted to assess nutrient dynamics of soils under old and young cocoa, coffee and cashew plantations and the leaf nutrient contents of the crops at Uhonmora, Edo State, Nigeria for proper cultural and soil fertility management of the plantations. Soil and crop leaf samples were collected from each plantation using random sampling technique. The samples were analyzed using standard procedures for sand, silt, clay, pH (H2O), electrical conductivity (EC), total N, available P, K, Ca, Mg, Na, Effective Cation Exchange Capacity (ECEC). Leaf samples were analyzed for N, P, K, Ca, Mg and Na. Data were compared with the corresponding soil and foliar critical nutrient values for each crop. Results indicated that the soils were texturally sandy clay loam and acidic. The soils varied in their nutrient contents, with soil P for the old cocoa, young coffee and cashew plantations far below critical values. The young cashew plot was low in N content but adequate for other plots. However, the soil ECEC increased with increase in calcium contents. Leaf N was below critical for all the crops. Leaf K was low for cocoa and coffee plants, leaf Ca was low for the young cashew plants, while leaf Mg was low for the young cocoa and old cashew. The high soil Mg/K ratio of 8.7- 22.3 as against the established value of 2.0 might have resulted in gross nutrient imbalance which must have affected the absorption and utilization of other nutrients. Hence, adequate soil N did not translate to availability of same to the crops. The ECEC showed that the soil needs to be improved upon for sustainable productivity. Soil nutrient content variation across the plantations with age of establishment will necessitate the need for consistent routine soil nutrient assessment for proper and balanced soil nutrient supply to the crops, for healthy crop growth and optimum yield. Management practices of soil surface mulching using organic wastes and cover crops under compatible cropping systems are needed for successful plot establishment and better growth performance of the young seedlings.Keywords: Alfisol,different ages, leaf nutrient content, micronutrient, plantation crops, soil nutrient content, soil [How to Cite: Joseph SO and RR Ipinmoroti. 2014. The Status of Micronutrient and Sulphur in Some Plantation Crops of Different Ages in an Alfisol in Southern Nigeria. J Trop Soils 19(2): 63-68. Doi: 10.5400/jts.2014.19.2.63]